Soil carbon stock in agroecosystems and secondary vegetation (Research, Society and Development, 2022)
The objective of the present work was to quantify soil carbon stock at different depths under agroecosystems and secondary vegetation area. The research was developed in the localities Caiana and Mata Redonda, belonging to the municipality of Remígio-PB. Four areas were selected, characterized according to the cultivation system in: conventional system, pasture, agroforestry system (SAF) and area with secondary vegetation. The experiment was carried out in a completely randomized design with a factorial arrangement [(3x3)+1], being the factors: cropping system (conventional, pasture and agroforestry system), depth (0-20; 20-40 and 40-60 cm) and an additional treatment corresponding to secondary vegetation. Organic carbon was extracted using the Walkley-Black method (oxidation-reduction), in which organic matter is oxidized using potassium dichromate. Organic matter was obtained by multiplying the carbon content by the constant 1,724. To determine the soil density (Ds) samples were collected with the aid of volumetric rings of 100 cm3 of internal volume from the layers 0-20, 20-40 and 40 to 60 cm. After collecting the samples, still in the field, the excess soil was removed from the edges of the rings, with the aid of a stylet. Then, the volumetric rings were sealed with cling film to avoid possible damage and deformation. Crop systems cause greater changes in chemical characteristics and soil carbon stock than secondary vegetation. The carbon stock is higher in the surface layer (0-20 cm) and in environments where the characteristics are closer to equilibrium, decreasing in depth.